Retaining Opportunities, Completing Key Projects with Remote Student Employees During COVID-19. Issue 2 (June 2021) - Handley, Henry; Harris, Kayla
As the field of higher education began furloughs and layoffs to alleviate COVID-19 budget concerns, cultural heritage workers were directed to clearly demonstrate how their work contributes to institutions' educational missions. Although physical library and archival collections were deemed inaccessible and less critical during the pandemic than ebooks, electronic journals, and digitized special collections, the two special collections projects considered in this case study demonstrate the value of continuing collections management work remotely and the relevance of student employees and other contingent workers in libraries and archives. The projects—one an inventory and bibliography of books acquired from a defunct religious library, and the other a review of digitized audio cassette tapes with little content information outside of the audio itself—enabled the retention of student workers facing few summer job opportunities and ineligibility for unemployment insurance, providing additional experience as well as compensation during an economic, as well as public health, crisis.